2018
DOI: 10.1111/and.13011
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation level of spermatozoa from subfertile and proven fertile and its relation to standard sperm parameters

Abstract: The epigenetic mechanism plays an important role in spermatogenesis such as DNA methylation where this episode is represented by either switching genes on or off. Twenty-eight samples (14 case and 14 controls) were subjected to Infinium 450K BeadChip arrays to identify genomic regions that differ in sperm DNA methylation patterns in the subfertile compared to the proven fertile group. Then two CpGs were validated by deep bisulphite sequencing on 82 sperm samples. The results screening study revealed eight CpGs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The current study demonstrated 60% of the DMRs have a decrease in DNA methylation, and 40% of DMRs an increase in DNA methylation, Additional file 4: Table S1. Therefore, a mixture of an increase and decrease in methylation is observed, which is distinct from the sperm hypermethylation observed in male infertility and aging [13,26,27]. Since all the paternal subjects were similar in age and fertile (Table 1), the current study observations appear to be distinct from infertility and aging-related DNA hypermethylation.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The current study demonstrated 60% of the DMRs have a decrease in DNA methylation, and 40% of DMRs an increase in DNA methylation, Additional file 4: Table S1. Therefore, a mixture of an increase and decrease in methylation is observed, which is distinct from the sperm hypermethylation observed in male infertility and aging [13,26,27]. Since all the paternal subjects were similar in age and fertile (Table 1), the current study observations appear to be distinct from infertility and aging-related DNA hypermethylation.…”
Section: Discussionmentioning
confidence: 48%
“…One factor that has been correlated with autism is paternal age [4,9,15] and sperm DNA methylation alterations [11,25]. Previous studies have shown a hypermethylation of sperm DNA is associated with male infertility, abnormal sperm parameters and increasing age [13,26,27]. Therefore, the majority of DMR involve an increase in DNA methylation when associated with infertility or age.…”
Section: Discussionmentioning
confidence: 99%
“…Contrariwise, incomplete or abnormal condensation of the sperm chromatin results in damaged DNA, leading to the impairment of egg cell fertilization and/or reduction in pregnancy rates (Benchaib et al, 2005;Miller et al, 2009;McSwiggin and O'Doherty, 2018). Considering these aspects, several studies have analyzed the gene and genome methylation levels of sperm DNA in association with male reproductive dysfunctions (Houshdaran et al, 2007;Rotondo et al, 2012Rotondo et al, , 2013Das et al, 2017;Alkhaled et al, 2018). These studies have mainly, but not only, investigated associations between improper DNA methylation in spermatozoa genome and negative variations in semen parameters, such as concentration (oligozoospermia), morphology (teratozoospermia), and progressive motility (asthenozoospermia), alone or in combinations, i.e., oligoasthenozoospermia (OA), oligoteratozoospermia, asthenoteratozoospermia (AT), and oligoasthenoteratozoospermia (OAT).…”
Section: Dna Methylation and Male Infertilitymentioning
confidence: 99%
“…The most thoroughly studied epigenetic modification is DNA methylation, which has emerged as a promising indicator of male infertility (Kumaresan et al, 2020). The mechanism behind DNA methylation is an addition of a methyl group to the 5th carbon of a cytosine immediately followed by a guanine (CpG dinucleotide) (Alkhaled et al, 2018; Urrego et al, 2014). Sperm DNA methylation signatures have been associated with the fertility status of bulls (Kropp et al, 2017), buffalo (Verma et al, 2014), and men (Alkhaled et al, 2018).…”
Section: Introductionmentioning
confidence: 99%